2022
DOI: 10.3390/ph15091116
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Facilities as Potential Reservoirs of Antimicrobial Resistant Klebsiella pneumoniae: An Emerging Concern to Public Health in Bangladesh

Abstract: The emergence of virulent extended spectrum β-lactamase producing Klebsiella pneumoniae (ESBL-KP) including carbapenem-resistant Klebsiella pneumoniae (CRKP) in hospital-acquired infections has resulted in significant morbidity and mortality worldwide. We investigated the antibiotic resistance and virulence factors associated with ESBL-KP and CRKP in tertiary care hospitals in Bangladesh and explored their ability to form biofilm. A total of 67 ESBL-KP were isolated from 285 Klebsiella pneumoniae isolates from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 84 publications
3
6
0
Order By: Relevance
“…Nevertheless, the prevalence of this gene particularly in Pakistan (n=162/1,033, 15.7%) was in-line with a study from several hospitals in the same country 42 . blaKPC is not common in Africa or South Asia 7,30 , which this study also confirmed; however, blaKPC was detected from neonatal cots in Tanzania in 2021 17 and blaKPC K. pneumoniae was found on pillows and the floor in three hospitals in Bangladesh 43 .…”
Section: Discussionsupporting
confidence: 77%
“…Nevertheless, the prevalence of this gene particularly in Pakistan (n=162/1,033, 15.7%) was in-line with a study from several hospitals in the same country 42 . blaKPC is not common in Africa or South Asia 7,30 , which this study also confirmed; however, blaKPC was detected from neonatal cots in Tanzania in 2021 17 and blaKPC K. pneumoniae was found on pillows and the floor in three hospitals in Bangladesh 43 .…”
Section: Discussionsupporting
confidence: 77%
“…Nevertheless, the prevalence of this gene, particularly in Pakistan (n = 162/ 1033, 15.7%), was in line with a study from several hospitals in the same country 41 . bla KPC is not common in Africa or South Asia 7,26 , which this study also confirmed; however, bla KPC was detected from neonatal cots in Tanzania in 2021 17 and bla KPC K. pneumoniae was found on pillows and the floor in three hospitals in Bangladesh 42 .…”
Section: Discussionsupporting
confidence: 76%
“…In the group of 160 ICU patients treated for COVID-19, Klebsiella pneumoniae ESBL or NDM strains were observed. The Klebsiella species are among the top 10 pathogens causing nosocomial bacterial infections ( Mahmud et al., 2022 ). No Klebsiella pneumoniae infection carbapenemase- (KPC-), VIM-, or IMP-type cases was reported in the aforementioned period.…”
Section: Discussionmentioning
confidence: 99%